# 7q+q-3q=-24?

Question:how do you solve this?

First, combine "like terms."
7q+q-3q = - 24
5q = -24

Then divide each side by 5.

5q/5 = -24/5

Solve for q.

q = -24/5 or - 4.8 ANSWER(S)

buena suerte
7q + q - 3q = 24

Add the 7q and q to get 8q

8q - 3q = 24

Subtract 3q from 8q to get 5q

5q = 24

Divide both sides of the equation by 5

q = 24/5

q= 4.8
step1
7q+q-3q=(7+1-3)q
step2
7+1-3=5 so
step 3
5q=-24
step4
q=-24/5=-4.8
1. Add all of the q's together

7q + q -3q = 5q

2. Then solve for q by dividing each side by 5

5q/5 = -24/5

q = -24/5 or -4.8
Nah dont worry! Its simple Algebra!

All u have to do is find the value of 'q'. Here is how u do it:

You add the variables on the left side and then solve for 'q' by dividing whatever the sum u get.

So its gonna be:

7q + q - 3q = -24

Note: If u have no number infront of a variable, that means there is a 1. So for this one, u see a 'q' alone, meaning there is a 1 attached to it. So u could also write it as '1q' for ur convenience to make life easier. But 'q' or '1q' is the same thing. Either way is fine. So anyway, now work through the problem

5q = -24

Divide by 5 on both sides

5q/5 = -24/5

The "5's" cancel on the left side leaving "q" alone while giving a value of q on the right side which is -24/5.

So q = -24/5. And thas ur answer! :)

Its really simple, just made it a bit long to explain u step by step.
there are two ways. Are you adding the variables or just adding the #'s? Well here is one way. if need more info email @ tyiprincess@yahoo.com

First Way Adding #'s... 7q+q-3q= -24 (Add the positive q's)( a single q = #1)
7q+q= 8q

So now your equation is: 8q-3q= -24 (Now subtract the q's)
8q-3q= 5q

equation: 5q= -24 (Now divide)
5q / 5=0 ( You divide # 5 not the q, becuz that is the variable that you are trying to find.. and what ever you do to one side you do the other)
-24 / 5= ( -4.8 or -4 4/5 this is your answer)

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.